Neonatal and Juvenile Ocular Development in Sprague-Dawley Rats: A Histomorphological and Immunohistochemical Study. Issue 2 (March 2018) - Vrolyk, Vanessa; Haruna, Julius; Benoit-Biancamano, Marie-Odile
As in many altricial species, rats are born with fused eyelids and markedly underdeveloped eyes. While the normal histology of the eyes of mature rats is known, the histomorphological changes occurring during postnatal eye development in this species remain incompletely characterized. This study was conducted to describe the postnatal development of ocular structures in Sprague-Dawley (SD) rats during the first month of age using histology and immunohistochemistry (IHC). Both eyes were collected from 51 SD rats at 13 time points between postnatal day (PND)1 and PND30. Histologic examination of hematoxylin and eosin-stained sections was performed, as well as IHC for cleaved-caspase-3 and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) to evaluate apoptosis, and IHC for Ki-67 and phospho-histone-H3 to evaluate cell proliferation. Extensive ocular tissue remodeling occurred prior to the eyelid opening around PND14 and reflected the interplay between apoptosis and cell proliferation. Apoptosis was particularly remarkable in the maturing subcapsular anterior epithelium of the lens, the inner nuclear and ganglion cell layers of the developing retina, and the Harderian gland, and was involved in the regression of the hyaloid vasculature. Nuclear degradation in the newly formed secondary lens fibers was noteworthy after birth and was associated with TUNEL-positive nuclear remnants lining the lens organelle-free zone. Cell proliferation was marked in the developing retina, cornea, iris, ciliary body and Harderian gland. The rat eye reached histomorphological maturity at PND21 after a rapid phase of morphological changes characterized by the coexistence of cell death and proliferation.